EVALUASI KINERJA PEMERINTAHAN DAERAH KOTA BATAM TAHUN ANGGARAN 2015 -2019 - Liauwi, Sandelia; Agus Munandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The research was to fulfilling the assignments, other than that also to analyseperformance of The Batam City’s Government through Their Financial Reports fromperiod of year 2015 until 2019. Evaluation of their performance will using financialratio analysing. And the results showed that decentralization analysis in average at43,92% and for financial autonomy at 81,31%. The research concluded thatperformance of The Batam City’s Government is good. But still need to increase therealization of Regional Original Revenue (PAD) for better result of decentralizationdegree.